Pengembangan Aplikasi KAGANGA Berbasis Android untuk Mengenalkan Aksara Sunda di Sekolah Dasar - Friska Siti Mutammimah; Ani Nur Aeni; Rana Gustian Nugraha (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The KAGANGA application was developed to introduce sundanese script based on android so that it can be a useful media in the learning process of sundanese script for grade V elementary school studentts. The purpose of this research was to develop the KAGANGA application and determine the efectiveness of using the KAGANGA application in the sundanese script learning process using this media. The research method used in this research is R&D (Research & Development) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques using interview, questionnaires, test, and documentation. Producing KAGANGA application with an average expert assesment of 93,75% and the result of media practibility get a result of 90,1% obtaining very feasible criteria and can be used in the learning process. The t-Test result show that the sig chance value of 0.000 obtained smaller than 0.05, so reject H0 which states that there is no difference thus, that there is a difference in the average pretest and posttest which means that KAGANGA media is effectively used in the sundanese script learning process. In the future, this media is expected to be used in learning sundanese script and can be useful to help teachers and students.